(untitled) (ModaPalavra e-periódico, 2014)
The current Zeitgeist - the spirit of the time - is an unrestricted pluralism with extremely rapid changes that reflect the current fashion. And fashion, as a business, is a complex mixture of personal, cultural, economic and social factors. Major part of the fashion industry meets market demand and align with them and, by creating business models that offer affordable novelties, the consumer starts to consume more and more, mainly throwaway products. On the other hand, another sector of the industry, the sustainable and ethical fashion, seeks to bring alternatives to this scenario in which sees solutions that bring limitations to the contemporary lifestyle, but propose lives that are worth living. How can the sustainable fashion enter this arena and snatch a share of this market?